The impact of giving support to others on older adults' perceived health status. Issue 1 (2nd December 2013) - Abolfathi Momtaz, Yadollah; Ibrahim, Rahimah; Hamid, Tengku A.
Abstract Background Social support that may contribute to the physical and mental health of older adults is widely studied. However, much of the existing research has focused on the impact of receiving support; the effects of giving support have largely been neglected. Using the biopsychosocial perspective, this study aimed to examine the independent impact of giving support to others on older adults' perceived health status. Methods Data for this study were obtained from a nationwide community‐based cross‐sectional survey entitled 'Determinants of Wellness among Older Malaysians: A Health Promotion Perspective', which was conducted in 2010. To assess the unique effects of giving support on perceived health status, above and beyond other possible known factors, a four‐step hierarchical regression model using SPSS was used to test the hypothesis. Results The findings from the analysis revealed that giving support to others was a significant positive predictor of older adults' perceived health status after receiving support, demographic variables and chronic medical conditions were considered. Further results showed that giving support to others had almost twice the effect on perceived health status (β = 0.11, P < 0.001) as receiving support (β = 0.06, P < 0.05). Conclusion The findings from this study underscore the need to develop programmes that encourage older adults' participation in productive activities such as caring for and helping others and volunteering.